Cantos epifânicos da paixão: a poesia lírico-amorosa em Ruy Espinheira Filho - Rego, Adriano Eysen (2007)
ABSTRACT This is an essay work whose theme is the lyric love poetry by Ruy Espinheira Filho, a native poet of Bahia of the 60s, born in 1942 in the city of Salvador. We selected a corpus of 22 poems from his published works, starting with Heléboro (1974) up to Elegias de agosto e outros poemas (2005). In a deeper study of the poetry by Espinheira, we perceive that Ruy possesses, like few contemporaneous poets, a lyric love through which gravitate images of women that are loved platonically and carnally. These are found in various poems created by a conscious lyric self of its feelings and capable of portraying the feminine in a rare balance of emotional and rational forces. In many poems, such as Canção da moça de dezembro , Poema de Novembro , Campo de Eros , Passionária , Soneto de Julho , Soneto para Safira Disparue , Soneto para Sandra , Segundo Soneto para Sandra , among others, we note a strong presence of the feminine body in a play of sensuality and erotism, since the words such as bellies , thighs , breasts portray the poet´s perception regarding the woman and her sensuality. In these perceptions the compassionate lips represent the alchemy of loving bodies.The poetry of love by the author of Heléboro is an amalgam of life and death, leading the writer to an ever-(re)visited memory. Desire, anxiety, anguish, pleasure, the lived and not-lived are being built in a poetic play that requires from the creator great ability in elaborating the verses. Ruy Espinheira makes possible the fusion of past, present and future times, triggering a dialogue between life, Eros and death , Thânatos, mythical forces that provide the creation of feminine images through desire, the realization of love, the unavoidable remembrance of women that, like ghosts. fill his mnemonic universe.